Made in China: Export competition and structural changes in the OECD countries - Matthias Flückiger; Markus Ludwig (University of Basel, Center of Business and Economics (WWZ), 2012)
This paper assesses the existence and extent of transition cost for the OECD economies associated with the increasing Chinese competition in the export markets. We find that intensified Chinese competition is an important factor in explaining structural changes not only within the manufacturing sector but also of the economies as a whole. In our empirical analysis which is guided by a simple extension of the Melitz Model we employ panel data at multiple levels of aggregation. The data reveal considerable adverse effects on export volume and industry-specific output in OECD countries as a result of increased Chinese competition. These distortions originating from the export market also affect structural variables within the manufacturing industries. Even at a regional level, changes in socioeconomic indicators can be associated with intensified Chinese export competition. Within the framework of our theoretical model, the mechanisms behind these observations are the following: The increased Chinese competition leads to a decline in exports and overall output, implying a decrease in average productivity and wages. This induces the reallocation of labor to the low-wage service sector, which in turn results in a reduction of average household income.
Keywords: F12; F14; F16; 330; China; Export Competition; Deindustrialization; Internationale Wirtschaft; China; Internationaler Wettbewerb; Handelseffekt; Strukturwandel; Deindustrialisierung; OECD-Staaten